Development of Information Literacy Worksheets Based on Guided Inquiry Approach on Acid-Base Material - Zia Nujunda Shaumi; Anissa Adiwena Putri; Wiwik Kartika Sari (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
The ease of accessing information can cause problems for students if the information obtained cannot be accounted for. Students’ information literacy can be improved through appropriate learning resources and learning media. The aims of this research is to develop teaching materials in the form of worksheets based on information literacy based on a guided inquiry approach on acid-base materials. This research uses the ADDIE development model which is carried out until the development stage. The data collection technique used a questionnaire to determine the feasibility and practicality of the worksheet. The feasibility of the worksheet was assessed by 3 expert validators. The interest and practicality of worksheet are assessed by the responses of students and teachers. The results of the validation test by experts are 85% in the very feasible category. The results of the response test of students and teachers were categorized as very interested and very practical with percentages of 92% and 91%, respectively. Based on the results of the assessment, information literacy worksheet based on a guided inquiry approach on acid-base material is very suitable to be used as acid-base teaching materials to improve information literacy.